Genetic variability in trait-specific rice germplasm groups based on coefficient of parentage, SSR markers and fertility restoration. Issue 1 (12th May 2014) - Khera, Pawan; Singh, Akhilesh Kumar; Priyadarshi, Rahul; Khandekar, Durga; Allu, Rajani K; Hiremath, Chitkale; Kumar, Raj; Mohan, Rashmi; Ulaganathan, K.; Shenoy, Vinay
Abstract : To maximize heterosis, it is important to understand the genetic diversity of germplasm and associate useful phenotypic traits such as fertility restoration for hybrid rice breeding. The objectives of the present study were to characterize genetic diversity within a set of rice germplasm groups using coefficient of parentage (COP) values and 58 simple sequence repeat (SSR) markers for 124 genotypes having different attributes such as resistance/tolerance to various biotic and abiotic stresses. These lines were also used for identifying prospective restorers and maintainers for wild abortive-cytoplasmic male sterile (CMS) line. The mean COP value for all the lines was 0.11, indicating that the genotypes do not share common ancestry. The SSR analysis generated a total of 268 alleles with an average of 4.62 alleles per locus. The mean polymorphism information content value was 0.53, indicating that the markers selected were highly polymorphic. Grouping based on COP analysis revealed three major clusters pertaining to the indica, tropical japonica and japonica lines. A similar grouping pattern with some variation was also observed for the SSR markers. Fertility restoration phenotype based on the test cross of the 124 genotypes with a CMS line helped identify 23 maintainers, 58 restorers and 43 genotypes as either partial maintainers or partial restorers. This study demonstrates that COP analysis along with molecular marker analysis might encourage better organization of germplasm diversity and its use in hybrid rice breeding. Potential restorers identified in the study can be used for breeding high-yielding stress-tolerant medium-duration rice hybrids, while maintainers would prove useful for developing new rice CMS lines.